Skeletal manifestations of hypoparathyroidism & spondylo-arthropathic features in hypoparathyroidism - Azad, Khan Abul Kalam; Hossain, Mohammad Zaid; Hussain, Tahmeed; Ahmad, Jamia; Abdullah, Md Shayekh; Islam, Mohammad Shaiful (Journal of Dhaka Medical College, 2013)
Hypoparathyroidism is a condition where level of parathyroid in blood is very low or undetectable. Hyporapathyroidism is associated with structural changes in bones and can present clinically with spondylo-articular features. This review focuses on the skeletal manifestations of hypoparathyroidism & spondylo-arthropathic features in hypoparathyroidism, understansding the histomorphological and microscopic changes in bone, spondylo-articular changes, and the diseases which mimic spondyloarticular features of hypoparathyroidism. Spondylo-articular features of hypoparathyroidism can resemble ankylosing spondylitis. It is important to differentiate hypoparathyroid-related spondyloarthropathy from ankylosing spondylitis because the management for the two disorders is different. The clinical profile, biochemical parameters, and radiological features aid in differential diagnosis. Studies have suggested several patterns to differentiate this clinical entity from ankylosing spondylitis. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15630 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 72-76